5‐HT2A receptor activation enhances NMDA receptor‐mediated glutamate responses through Src kinase in the dendrites of rat jaw‐closing motoneurons. (11th April 2019) - Dantsuji, Masanori; Nakamura, Shiro; Nakayama, Kiyomi; Mochizuki, Ayako; Park, Sook Kyung; Bae, Yong Chul; Ozeki, Masahiko; Inoue, Tomio
Abstract : Key points: 5‐HT increases the excitability of brainstem and spinal motoneurons, including the jaw‐closing motoneurons, by depolarizing the membrane potential and decreasing the medium‐duration afterhyperpolarization. In this study, we focused on how 5‐HT enhances postsynaptic glutamatergic responses in the dendrites of the jaw‐closing motoneurons. We demonstrate that 5‐HT augments glutamatergic signalling by enhancing the function of the GluN2A‐containing NMDA receptor (NMDAR) through the activation of 5‐HT2A receptors (5‐HT2A Rs) and Src kinase. To enhance glutamatergic responses, activation of the 5‐HT2A Rs must occur within ∼60 μm of the location of the glutamate responses. 5‐HT inputs to the jaw‐closing motoneurons can significantly vary their input–output relationship, which may contribute to wide‐range regulation of contractile forces of the jaw‐closing muscles. Abstract: Various motor behaviours are modulated by 5‐HT. Although the masseter (jaw‐closing) motoneurons receive both glutamatergic and serotonergic inputs, it remains unclear how 5‐HT affects the glutamatergic inputs to the motoneuronal dendrites. We examined the effects of 5‐HT on postsynaptic responses evoked by single‐ or two‐photon uncaging of caged glutamate (glutamate responses) to the dendrites of masseter motoneurons in postnatal day 2–5 rats of either sex. Application of 5‐HT induced membrane depolarization and enhanced the glutamate‐response amplitude. This enhancement was mimicked by the 5‐HT2A receptor (5‐HT2A R) agonist and was blocked by the 5‐HT2A/2C R antagonist. However, neither the 5‐HT2B R nor the 5‐HT2C R agonists altered glutamate responses. Blockade of the NMDA receptors (NMDARs), but not AMPA receptors, abolished the 5‐HT‐induced enhancement. Furthermore, the selective antagonist for the GluN2A subunit abolished the 5‐HT‐induced enhancement. 5‐HT increased GluN2A phosphorylation, while the Src kinase inhibitor reduced the 5‐HT‐induced enhancement and GluN2A phosphorylation. When exposure to the 5‐HT2A R agonist was targeted to the dendrites, the enhancement of glutamate responses was restricted to the loci of the dendrites near the puff loci. Electron microscopic immunohistochemistry revealed that both the NMDARs and the 5‐HT2A Rs were close to each other in the same dendrite. These results suggest that activation of dendritic 5‐HT2A Rs enhances the function of local GluN2A‐containing NMDARs through Src kinase. Such enhancement of the glutamate responses by 5‐HT may contribute to wide‐range regulation of contractile forces of the jaw‐closing muscles. Key points: 5‐HT increases the excitability of brainstem and spinal motoneurons, including the jaw‐closing motoneurons, by depolarizing the membrane potential and decreasing the medium‐duration afterhyperpolarization. In this study, we focused on how 5‐HT enhances postsynaptic glutamatergic responses in the dendrites of the jaw‐closing motoneurons. We demonstrate that 5‐HT augments glutamatergic signalling by enhancing the function of the GluN2A‐containing NMDA receptor (NMDAR) through the activation of 5‐HT2A receptors (5‐HT2A Rs) and Src kinase. To enhance glutamatergic responses, activation of the 5‐HT2A Rs must occur within ∼60 μm of the location of the glutamate responses. 5‐HT inputs to the jaw‐closing motoneurons can significantly vary their input–output relationship, which may contribute to wide‐range regulation of contractile forces of the jaw‐closing muscles.